PENGARUH KONSEP DIRI TERHADAP HASIL BELAJAR EKONOMI SISWA SMA PERTIWI 2 PADANG DENGAN MOTIVASI BELAJAR SEBAGAI VARIABEL INTERVENING - Maharani, Intan - (Pendidikan Ekonomi, 2014)
The research was motivated by low economic students learning outcomes in Senior High School Pertiwi 2 Padang. This is because the low self-concept student and studentâs motivation. This study aims to determine whether there is influence of self-concept on learning outcomes of studentâs economic in Senior High School Pertiwi 2 Padang with motivation as an Intervening Variable.This type of research is a descriptive correlational. The study population was all students majoring in social studies class XI in Senior High School Pertiwi 2 Padang. This is sample of students majoring in social studies class XI in Senior High School Pertiwi 2 Padang, amounting to 94 people. Research instrument used in this study was a questionnaire. To determine the effect of self-concept on learning outcomes with motivation to learn as an intervening variable regression analysis was used intervening variables.Based on the results of the analysis show that ; (1) The concept of self positive effect on learning outcomes of students in Senior High School Pertiwi 2 Padang means the better the self-concept of students learning so the better results obtained.(2) The concept of self positive effect on learning outcomes of students in Senior High School Pertiwi 2 Padang means the better the self-concept of student learning so the higher the studentâs motivation to learn. (3) Motivation to learn positive effect on student learning outcomes in Senior High School Pertiwi 2 Padang means the higher the studentâs motivation to learn, the better the learning outcomes obtained. (4) The concept of self influence on student learning outcomes in Senior High School 2 Padang with motivation to learn as an intervening variable.To improve student learning outcomes in Senior High School Pertiwi 2 Padang, researchers suggest to all parties first school teacher should pay more attention to studentâs self-concept by creating learning situations that provide opportunities for students to obtain reinforcement and always positive thinking about students, Thus students motivation will increase and student learning result will increase too.